Pelatihan Metode Pembelajaran Fun English Games Using Application bagi Guru Bahasa Inggris Mas Nu Batahan - Resdilla Pratiwi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
This article deals with the training of Fun English Games Learning Method for English Teacher in MAS NU Batahan, This article shows several learning methods by using English Games funny and easy to understand, such as, Word Connect Application, Spelling Bee application, Stop the Clock Application, Typing Paragraphs for speed. This activity intends to enlarge some learning methods by using English Games for fun, and to give comprehending that English learning’s easy and enjoying. The method of this study used community development that collaborating theory and practicing in which using fun English games learning method in teaching English for English teacher MAS NU Batahan. The result shows that Fun English Games learning Method’s successfully applied in the classroom, the students are happy and can understand English learning easily and quickly through Fun English Games Method. It has benefit for teachers in teaching 4 skill, reading, writing, speaking and listening that must be mastered by students. In addition, School can use this method to improve the quality of learning in achieving very satisfactory results. Based on the explanation above can be concluded that Fun English Games learning Method for English teachers is very useful dan helpful in teaching and learning process.